Fairy tales for bedtime - Dickins, Rosie; Ragondet, Nathalie (Usborne London, 2013)
An illustrated and bound collection of traditional stories, freshly retold for today's children. It is presented in luxurious cloth quarter-binding, with ribbon marker and carefully designed pages. It is written for reading aloud to young children, or for older children to read themselves.